Moderate restriction of macrophage-tropic human immunodeficiency virus type 1 by SAMHD1 in monocyte-derived macrophages. - Kahoru Taya; Emi E Nakayama; Tatsuo Shioda (PLoS ONE)
Macrophage-tropic human immunodeficiency virus type 1 (HIV-1) strains are able to grow to high titers in human monocyte-derived macrophages. However, it was recently reported that cellular protein SAMHD1 restricts HIV-1 replication in human cells of the myeloid lineage, including monocyte-derived macrophages. Here we show that degradation of SAMHD1 in monocyte-derived macrophages was associated with moderately enhanced growth of the macrophage-tropic HIV-1 strain. SAMHD1 degradation was induced by treating target macrophages with vesicular stomatitis virus glycoprotein-pseudotyped human immunodeficiency virus type 2 (HIV-2) particles containing viral protein X. For undifferentiated monocytes, HIV-2 particle treatment allowed undifferentiated monocytes to be fully permissive for productive infection by the macrophage-tropic HIV-1 strain. In contrast, untreated monocytes were totally resistant to HIV-1 replication. These results indicated that SAMHD1 moderately restricts even a macrophage-tropic HIV-1 strain in monocyte-derived macrophages, whereas the protein potently restricts HIV-1 replication in undifferentiated monocytes.